xperimental Evaluation of the Possibility of using the LAL test to Determine Bacterial Endotoxins in Vaccines for Rabies Prophylaxis - A. V. Muhacheva; O. A. Barkhaleva; O. V. Shapovalova; N. P. Neugodova; A. Yu. Butirskiy; A. A. Movsesyants; R. A. Volkova; K. A. Sarkisyan (Эпидемиология и вакцинопрофилактика, 2021)
Relevance. The presence of pyrogenic impurities in finished dosage forms of concentrated cultural anti-rabies vaccines produced in the Russian Federation is determined using pyrogenicity tests on rabbits (in vivo). In accordance with the decision of the Board of the Eurasian Economic Commission dated September 7, 2018 N 151 «On the approval of guidelines for drawing up a regulatory document on the quality of a medicinal product», one of the requirements for parenteral drugs is the determination of bacterial endotoxins. This document indicates that the regulatory documentation should include a test and an admissibility criterion for bacterial endotoxins (BE) using the horseshoe crab amoebocyte lysate technique.Aims. Experimental evaluation of the possibility of using the LAL-test to determine bacterial endotoxins in national vaccines for the prevention of rabies.Materials and methods. The research of the drug «Cultural antirabies vaccine concentrated inactivated purified» of national production was carried out in accordance with the National Pharmacopoeia of the Russian Federation, General Pharmacopoeia Monograph OFS.1.2.4.0006.15 in three modifications: gel-clot test: methods A, B; turbidimetric kinetic test: method C; chromogenic kinetic test: method D.Results. Was investigated 6 series of the national vaccines for the prevention of rabies from two national manufacturers (using three pharmacopoeial methods). LAL reagent produced by two companies (Charles River Endosafe® and Lonza). In order to confirm the reproducibility of the method, the gel-clot test was carried out at different time intervals by one or two operators. During the research was determined the possibility of using photometric methods (method C and D).Conclusions. The research proved the possibility of determining bacterial endotoxins by methods: gel-clot test (method A), turbidimetric kinetic test (method C) and chromogenic kinetic test (method D). Method B is recommended for quantitative analysis of vaccine without instrumental methods. During the research all national vaccines for the prevention of rabies was free from bacterial endotoxins (no more 25 EU/ml).